Correlation of high critical heat flux during flow boiling for water in a small tube at various subcooled conditions. (March 2017) - Shibahara, M.; Fukuda, K.; Liu, Q.S.; Hata, K.
Abstract: High critical heat fluxes (CHFs) for subcooled boiling of water in a small tube were investigated experimentally. A platinum tube with an inner diameter of 1.0 mm and a length of 40.9 mm was used in the experiment. The upward flow velocity, the subcooling of water, and the outlet pressure of the experimental tube were varied to enable a parametric study of the CHFs. The flow velocity ranged from 9 to 13 m/s and the inlet subcooling ranged from 69 to 148 K. The boiling number decreased with increasing Weber number. The boiling number is also dependent on a non-dimensional parameter and the density ratio of liquid to vapor. A correlation for the high CHF of the small tube was obtained based on the experimental data. Finally, the high CHF correlation was evaluated using the CHF data obtained by other researchers. Highlights: The boiling number decreased with increasing Weber number. The boiling number is dependent on Weber number, a non-dimensional parameter and the density ratio of liquid to vapor. A correlation for the high CHF of the small tube was obtained. The experimental data were within ± 15% of the authors' correlation.